Solid-state electrolyte prepolymerization liquid and method for preparing solid-state battery by applying solid-state electrolyte prepolymerization liquid

By using a solid electrolyte prepolymer in an all-solid-state battery to polymerize the prepolymer in situ within the battery, the problems of poor lithium-ion transport capacity and high solid-solid interface impedance are solved, resulting in a solid-state battery with high safety and long cycle life.

CN121097193APending Publication Date: 2025-12-09NINGBO GRAPHENE INNOVATION CENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511230554.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-29
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing all-solid-state batteries have poor lithium-ion transport capabilities, and poor solid-solid contact between the solid electrolyte and the electrodes results in high interfacial impedance, which affects battery safety performance and cycle life.

Method used

A solid electrolyte prepolymer was prepared by dissolving polyethylene glycol diacrylate monomer, fluorinated acrylate monomer, lithium salt and initiator in electrolyte. The solid electrolyte was then prepared in the battery through in-situ polymerization of the prepolymer. The solid electrolyte prepolymer was then polymerized in-situ inside the battery to form a solid electrolyte that diffuses on the surface and inside the positive and negative electrodes and the separator, thereby reducing the solid-solid contact interface resistance.

Benefits of technology

It improves battery safety and lithium-ion transport rate, enhances battery cycle life and safety performance, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a solid electrolyte prepolymerization solution which comprises an electrolyte, a polyethylene glycol diacrylate monomer, a fluorinated acrylate monomer and an initiator. The solid electrolyte prepolymerization liquid can solve the problem that the transmission rate of lithium ions in a battery is low. The polymer solid-state battery is prepared by combining a solid-state electrolyte prepolymerization solution with an in-situ curing process, a non-volatile polymer solid-state electrolyte with high lithium ion conductivity is used for replacing an electrolyte, and in-situ polymerization is initiated under heating and pressurizing conditions to prepare the solid-state battery, so that the solid-state electrolyte is diffused on the surfaces and the interiors of a positive electrode, a negative electrode and a diaphragm; the solid-solid contact interface impedance is reduced, and meanwhile, the safety performance of the battery is greatly improved. Meanwhile, the polymer solid electrolyte three-dimensional network can effectively prolong the cycle life of the battery; by adopting an in-situ polymerization process, large-scale production is facilitated, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] This invention relates to the field of lithium-ion battery preparation technology, specifically to a solid electrolyte prepolymer and a method for preparing solid-state batteries using the same. Background Technology

[0003] The development from liquid lithium-ion batteries to high-energy-density solid-state batteries will bring about a series of changes in material systems and manufacturing processes, requiring breakthroughs in corresponding key technologies. All-solid-state batteries, with their high energy density and high safety, have attracted considerable attention from researchers. However, the lack of electrolyte wetting results in poor lithium-ion transport within the battery, and the poor solid-solid contact between the solid electrolyte and the electrodes leads to higher interfacial impedance. Summary of the Invention

[0004] The present invention aims to at least partially overcome the above-mentioned and / or other potential problems existing in the prior art: to provide a solid electrolyte prepolymer and a method for preparing solid-state batteries using the same. The present invention first uses polyethylene glycol diacrylate monomer, fluorinated acrylate monomer, lithium salt, and initiator dissolved in an electrolyte to obtain a solid electrolyte prepolymer. This prepolymer is added to the battery during the battery filling process, and in-situ polymerization is initiated under heating and pressurization conditions to obtain a solid-state battery. This achieves solid electrolyte diffusion on the surface and inside of the positive and negative electrodes and the separator, reducing the solid-solid contact interface impedance while significantly improving battery safety performance.

[0005] The technical solution of the present invention is as follows: a solid electrolyte prepolymer liquid, comprising an electrolyte, polyethylene glycol diacrylate monomer, fluoroacrylate monomer, and an initiator.

[0006] As an optimization, the mass ratio of the fluorinated acrylate monomer to the polyethylene glycol diacrylate monomer is 1:(1-4).

[0007] As an optimization, the initiator is one or both of benzoyl peroxide (BPO) and azobisisobutyronitrile (AIBN).

[0008] As an optimization, the fluoroacrylate monomer is one of trifluoroethyl acrylate, trifluoroethyl methacrylate, hexafluorobutyl acrylate, hexafluorobutyl methacrylate, and perfluoroalkyl ethyl acrylate.

[0009] As an optimization, the electrolyte is a commercially available finished electrolyte.

[0010] Preferably, the electrolyte is either the LD-1320B electrolyte produced by Xiamen ShouNeng Technology Co., Ltd. or the LB-301 electrolyte produced by Zhangjiagang Guotai Huarong Chemical New Materials Co., Ltd.

[0011] The present invention provides a solid-state battery, wherein the electrolyte is obtained by in-situ polymerization and solidification of the solid electrolyte prepolymer liquid.

[0012] The present invention also provides a method for preparing a solid-state battery using the aforementioned solid electrolyte prepolymer solution. The solid electrolyte prepolymer solution is injected into the battery to impregnate the positive electrode material and the negative electrode material, and then hot-pressed to polymerize to form a solid electrolyte, thereby obtaining a solid-state battery.

[0013] As an optimization, the method for preparing solid-state batteries specifically includes the following steps: 1) A solid electrolyte prepolymer is obtained by mixing electrolyte, polyethylene glycol diacrylate monomer, fluorinated acrylate monomer and initiator; 2) Assemble and encapsulate the battery cell using positive electrode material, negative electrode material and separator, then inject the solid electrolyte prepolymer liquid obtained in step 1) into the battery cell to impregnate the positive electrode material and negative electrode material, and then form a solid electrolyte by hot pressing polymerization to obtain a solid battery. Preferably, the areal density of the positive electrode material is in the range of 20-25 mg / cm³. 2 The compacted density is 3.0-3.5 g / cm³. 3 .

[0014] Preferably, the areal density of the negative electrode material is in the range of 6-8 mg / cm³. 2 The compacted density is 1.0-1.5 g / cm³. 3 .

[0015] Preferably, the solid-state battery prepared in step 2) is also subjected to high-temperature formation.

[0016] Preferably, the negative electrode material is one or a mixture of two of the silicon-carbon composite negative electrode material from Ningbo Fuli Battery Materials Technology Co., Ltd. and the graphite negative electrode material from BTR New Materials Group Co., Ltd.

[0017] Preferably, the negative electrode material is a composite silicon-carbon graphite material made by mixing silicon-carbon composite negative electrode material from Ningbo Fuli Battery Materials Technology Co., Ltd. and graphite negative electrode material from BTR New Materials Group Co., Ltd. in a mass ratio of (9-0.1):1.

[0018] Preferably, the soaking time in step 2) is 12-48 hours.

[0019] The beneficial effects of this invention are as follows: The solid electrolyte prepolymer of this invention can improve the problem of slow lithium-ion transport rate inside the battery. Polymer solid-state batteries are prepared by combining the solid electrolyte prepolymer with an in-situ curing process. A non-volatile polymer solid electrolyte with high lithium-ion conductivity replaces the electrolyte. In-situ polymerization is initiated under heating and pressurization conditions to obtain a solid-state battery. This allows the solid electrolyte to diffuse across the surface and interior of the positive and negative electrodes and the separator, reducing the solid-solid contact interface impedance and significantly improving battery safety performance. Simultaneously, the three-dimensional network of the polymer solid electrolyte can effectively improve the battery's cycle life. Furthermore, the in-situ polymerization process of this invention facilitates large-scale production and reduces production costs. Attached Figure Description

[0020] Figure 1 Cycle capacity diagrams of four batteries prepared under the same conditions for Example 1.

[0021] Figure 2 Cycle capacity diagrams of three batteries prepared under the same conditions for Example 2.

[0022] Figure 3 Cycle capacity diagrams of four batteries prepared under the same conditions for Comparative Example 1.

[0023] Figure 4 Cycle capacity diagram of the battery prepared for Comparative Example 2.

[0024] Figure 5 Cycle capacity diagrams of four batteries prepared under the same conditions for Comparative Example 3.

[0025] Figure 6 This is a schematic diagram of the existing battery cell structure. Detailed Implementation

[0026] The present invention will be further described in detail below with reference to specific embodiments, but the present invention is not limited to the following specific embodiments.

[0027] Electrolyte No. 1 is LD-1320B produced by Xiamen ShouNeng Technology Co., Ltd., and electrolyte No. 2 is LB-301 produced by Zhangjiagang Guotai Huarong Chemical New Materials Co., Ltd. The composite silicon-carbon-graphite is a mixture of silicon-carbon composite anode material from Ningbo Fuli Battery Materials Technology Co., Ltd. and graphite anode material from BTR New Materials Group Co., Ltd., at a mass ratio of (9-0.1):1.

[0028] Example 1 (1) In an argon-filled glove box, 0.5 g of PEGDA (polyethylene glycol diacrylate), 0.3 g of fluoroacrylate, 0.016 g of AIBN (azobisisobutyronitrile), and 10 g of electrolyte No. 1 are mixed evenly to obtain a liquid-flowing prepolymer.

[0029] (2) Pour the prepared prepolymer solution into a small glass bottle and stir well; (3) In a low dew point room, 22-face-load NCA is used as the positive electrode, and composite silicon-carbon graphite is used as the negative electrode and 1631 model porous diaphragm produced by Yunnan Enjie New Material Co., Ltd. is used to assemble soft-pack cells. (4) Using the prepolymer solution prepared in step (1) as the electrolyte, a 5Ah soft-pack battery is assembled using existing technology; the soft-pack battery is prepared by stacking and the electrode tabs are welded and the aluminum-plastic film is encapsulated and the electrolyte is injected. The battery structure is as follows: Figure 6 As shown, this is consistent with existing technology.

[0030] (5) After assembly, the solid lithium battery was soaked at room temperature for 48 hours and cured for 24 hours at 60°C and 0.038 MPa using a hot pressing machine with existing technology to obtain the in-situ polymerized solid lithium battery. The formation process was as follows: first charge at 0.05C for 2 hours, then charge at 0.1C with a cutoff voltage of 3.4V, charge at 0.2C with a cutoff voltage of 3.8V, and charge and discharge at 0.33C at room temperature for 1 week. (6) The lithium battery prepared in step (5) was subjected to high-temperature formation at 45°C. The formation process was as follows: first, it was charged at 0.05C for 2 hours, the cutoff voltage of 0.1C was 3.4V, the cutoff voltage of 0.2C was 3.8V, and it was charged and discharged at 0.33C at room temperature for 1 week. (7) Further, the lithium batteries after formation were subjected to a 0.33C charge-discharge test, with a voltage range of 2.5-4.35V. The battery energy density was ≥300Wh / kg, and the capacity retention rate after 200 cycles was 93.8%. Batteries 1-4 were prepared according to the steps of this embodiment, and the cycle performance of the four batteries was measured as follows: Figure 1 As shown.

[0031] Example 2 (1) In an argon-filled glove box, 0.5 g of PEGDA (polyethylene glycol diacrylate), 0.3 g of fluoroacrylate, 0.016 g of AIBN (azobisisobutyronitrile), and 10 g of electrolyte No. 2 are mixed evenly to obtain a liquid-flowing prepolymer.

[0032] (2) Pour the prepared prepolymer solution into a small glass bottle and stir well; (3) In a low dew point room, 22-face-load NCA is used as the positive electrode, and composite silicon-carbon graphite is used as the negative electrode and 1631 model porous diaphragm produced by Yunnan Enjie New Material Co., Ltd. is used to assemble soft-pack cells. (4) Use the polymer electrolyte prepolymer liquid prepared in step (1) as the electrolyte to assemble a 5Ah soft pack battery; (5) After assembly, the solid lithium battery was soaked at room temperature for 48 hours and then cured for 24 hours at 60°C and 0.038 MPa using a hot pressing formation machine to obtain the solid lithium battery polymerized in situ. The formation process was as follows: first, charge at 0.05C for 2 hours, then charge at 0.1C with a cutoff voltage of 3.4V, then charge at 0.2C with a cutoff voltage of 3.8V, and then charge and discharge at 0.33C at room temperature for 1 week. (6) The lithium battery prepared in step (5) was subjected to high-temperature formation at 45°C. The formation process was as follows: first, it was charged at 0.05C for 2 hours, the charging cutoff voltage was 3.4V at 0.1C, the charging cutoff voltage was 3.8V at 0.2C, and then charged and discharged at room temperature at 0.33C for 1 week. (7) Further, the formed lithium batteries were subjected to a 0.33C charge-discharge test with a voltage range of 2.5-4.35V. The battery energy density was ≥290Wh / kg, and the capacity retention rate after 135 cycles was 91.6%. Batteries 1-3 were prepared according to the steps of this embodiment, and the cycle performance of the three batteries was measured as follows: Figure 2 As shown.

[0033] Comparative Example 1 (1) In a low dew point room, 22-face-load NCA is used as the positive electrode, and composite silicon-carbon graphite is used as the negative electrode and 1631 model porous diaphragm produced by Yunnan Enjie New Material Co., Ltd. is used to assemble soft-pack cells. (2) In a glove box filled with argon, inject 10 g of electrolyte No. 1 into the cell to assemble a 5Ah soft pack battery; (3) After assembly, soak at room temperature for 48 hours; (4) The lithium battery prepared in step (3) was subjected to high-temperature formation at 45°C. The formation process was as follows: first, it was charged at 0.05C for 2 hours, the charging cutoff voltage was 3.4V at 0.1C, the charging cutoff voltage was 3.8V at 0.2C, and then charged and discharged at 0.33C at room temperature for 1 week. (5) Furthermore, the formed lithium batteries were subjected to a 0.33C charge-discharge test with a voltage range of 2.5-4.35V. The battery energy density was ≥309Wh / kg, and the capacity retention rate after 200 cycles was only 40%. Batteries 1-4 were prepared according to the steps of this comparative example, and the cycle performance of the four batteries was measured as follows: Figure 3 As shown.

[0034] Comparative Example 2 (1) In a low dew point room, 22-face-load NCA is used as the positive electrode, and composite silicon-carbon graphite is used as the negative electrode and 1631 model porous diaphragm produced by Yunnan Enjie New Material Co., Ltd. is used to assemble soft-pack cells. (2) In a glove box filled with argon, inject 10 g of electrolyte No. 2 into the cell to assemble a 5Ah soft pack battery; (3) After assembly, soak at room temperature for 48 hours; (4) The lithium battery prepared in step (3) was subjected to high-temperature formation at 45°C. The formation process was as follows: first, it was charged at 0.05C for 2 hours, the charging cutoff voltage was 3.4V at 0.1C, the charging cutoff voltage was 3.8V at 0.2C, and then charged and discharged at 0.33C at room temperature for 1 week. (5) Furthermore, the formed lithium battery was subjected to a 0.33C charge-discharge test with a voltage range of 2.5-4.35V. The battery energy density was ≥298Wh / kg, and the capacity retention rate after 140 cycles was only 63.4%. The cycle performance was as follows: Figure 4 As shown.

[0035] Comparative Example 3 (1) In an argon-filled glove box, 0.5 g of PEGDA (polyethylene glycol diacrylate), 0.3 g of fluoroacrylate, 0.016 g of AIBN (azobisisobutyronitrile), and 10 g of electrolyte No. 1 are mixed evenly to obtain a liquid-flowing prepolymer.

[0036] (2) Pour the prepared prepolymer solution into a small glass bottle and stir well; (3) In a low dew point room, 22-face-load NCA is used as the positive electrode, and composite silicon-carbon graphite is used as the negative electrode and 1631 model porous diaphragm produced by Yunnan Enjie New Material Co., Ltd. is used to assemble soft-pack cells. (4) Use the polymer electrolyte prepolymer liquid prepared in step (1) as the electrolyte to assemble a 5Ah soft pack battery; (5) After assembly, the solid lithium battery was soaked at room temperature for 48 hours and then cured for 24 hours using a hot pressing machine at 60°C and 0.038 MPa to obtain the in-situ polymerized solid lithium battery. (6) The lithium battery prepared in step (5) was formed at room temperature. The formation regime was: 0.05C charge and discharge for 1 week, 0.1C charge and discharge for 2 weeks. The battery energy density at 0.05C was 330Wh / kg, and the battery energy density at 0.1C was 323Wh / kg. (7) Further, the formed lithium batteries were subjected to a 0.33C charge-discharge test with a voltage range of 2.5-4.35V. The battery energy density was ≥300Wh / kg, and the capacity retention rate after 200 cycles was 92.3%. Batteries 1-4 were prepared according to the steps of this comparative example, and the cycle performance of the four batteries was measured as follows: Figure 5 As shown.

[0037] from Figure 1 , 2 Comparing the battery capacity retention rates over 200 cycles, Example 1 > Example 2, it can be seen that the high-temperature and high-pressure formation process can improve the battery capacity retention rate.

[0038] from Figure 1 ,3 The comparison shows that electrolyte No. 1 has a discharge capacity of 209 mAh / g, while electrolyte No. 2 has a discharge capacity of 196.5 mAh / g, with the former being significantly better than the latter.

[0039] from Figure 1 , 4 The comparison shows that, using electrolyte No. 1, the cycle life of solid-state batteries is much longer than that of traditional liquid batteries.

[0040] from Figure 3 , 5 The comparison shows that, using electrolyte No. 2, the cycle life of solid-state batteries is much longer than that of traditional liquid batteries.

[0041] from Figure 1-5 As can be seen, the batteries prepared by this invention have good consistency.

[0042] The above are merely exemplary embodiments of the present invention and do not constitute any limitation on the scope of protection of the present invention. All technical solutions formed by equivalent exchange or substitution fall within the scope of protection of the present invention.

Claims

1. A solid electrolyte prepolymer solution, characterized in that, It includes electrolyte, polyethylene glycol diacrylate monomer, fluoroacrylate monomer, and initiator.

2. The solid electrolyte prepolymer solution according to claim 1, characterized in that, The mass ratio of the fluorinated acrylate monomer to the polyethylene glycol diacrylate monomer is 1:(1-4).

3. The solid electrolyte prepolymer solution according to claim 2, characterized in that, The initiator is one or both of benzoyl peroxide (BPO) and azobisisobutyronitrile (AIBN).

4. The solid electrolyte prepolymer solution according to claim 3, characterized in that, The fluoroacrylate monomer is one of trifluoroethyl acrylate, trifluoroethyl methacrylate, hexafluorobutyl acrylate, hexafluorobutyl methacrylate, and perfluoroalkyl ethyl acrylate.

5. A solid-state battery, characterized in that, Its electrolyte is obtained by in-situ polymerization and solidification of the solid electrolyte prepolymer liquid.

6. A method for preparing a solid-state battery using the solid electrolyte prepolymer solution according to any one of claims 1-4, characterized in that, Solid electrolyte prepolymer is injected into the battery to impregnate the positive and negative electrode materials, and then hot-pressed to polymerize to form a solid electrolyte, thus obtaining a solid battery.

7. The method for preparing a solid-state battery according to claim 6, characterized in that, Specifically, the following steps are included: 1) A solid electrolyte prepolymer is obtained by mixing electrolyte, polyethylene glycol diacrylate monomer, fluorinated acrylate monomer and initiator; 2) Assemble and encapsulate the battery cell using positive electrode material, negative electrode material and separator, then inject the solid electrolyte prepolymer liquid obtained in step 1) into the battery cell to impregnate the positive electrode material and negative electrode material, and then form a solid electrolyte by hot pressing polymerization to obtain a solid battery.

8. The method for preparing a solid-state battery according to claim 7, characterized in that, The areal density of the positive electrode material ranges from 20 to 25 mg / cm³. 2 The compacted density is 3.0-3.5 g / cm³. 3 The areal density of the negative electrode material ranges from 6 to 8 mg / cm³. 2 The compacted density is 1.0-1.5 g / cm³. 3 .

9. The method for preparing a solid-state battery according to claim 8, characterized in that, It also includes high-temperature formation of the solid-state battery prepared in step 2).

10. The method for preparing a solid-state battery according to claim 9, characterized in that, The negative electrode material is a composite silicon-carbon graphite material formed by mixing silicon-carbon composite negative electrode material and graphite negative electrode material in a mass ratio of (9-0.1):1.